1992
DOI: 10.1111/j.1439-0329.1992.tb00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the life cycle of Gremmeniella abietina on Scots pine in southern Sweden

Abstract: Aspects of the life cycle of Gremmeniella abietina (Lagerb.) Morelet were studied from 1988 to 1990 in stands oi Pinus sylvestris L., 16-32 years old, in southern Sweden, initiated in 1988 with a widespread outbreak of the disease. Pycnidia started to release conidia in late spring and apothecia began to release ascospores in summer. Latent infections could still be detected one year after their establishment by cultivation of healthy looking shoots on agar petri dishes. G. abietina appeared to have a mainly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…Witzell, A. Bernhold and P. Hansson The results of this study show that the vitality of G. abietina conidia in P. sylvestris slash on ground in northern boreal areas remain high the entire period from felling of infected trees until conidia dispersal. This saprotrophic ability agrees with earlier findings from Fennoscandia, concluding that G. abietina can survive and reproduce for at least 2 years in dead shoots of living trees (Hellgren and Barklund 1992;Kaitera et al 1997), and even longer in cankers (Kurkela 1981;Witzell 2001). Our results are also similar to those of Dorworth (1972) who showed that apothecia of the North American race of G. abietina are able to survive for at least 10 months on Pinus resinosa slash.…”
supporting
confidence: 95%
See 1 more Smart Citation
“…Witzell, A. Bernhold and P. Hansson The results of this study show that the vitality of G. abietina conidia in P. sylvestris slash on ground in northern boreal areas remain high the entire period from felling of infected trees until conidia dispersal. This saprotrophic ability agrees with earlier findings from Fennoscandia, concluding that G. abietina can survive and reproduce for at least 2 years in dead shoots of living trees (Hellgren and Barklund 1992;Kaitera et al 1997), and even longer in cankers (Kurkela 1981;Witzell 2001). Our results are also similar to those of Dorworth (1972) who showed that apothecia of the North American race of G. abietina are able to survive for at least 10 months on Pinus resinosa slash.…”
supporting
confidence: 95%
“…The aim of this study was to investigate the survival and vitality of G. abietina in slash of clear-cut P. sylvestris stands infected by G. abietina in northern Sweden, and to determine an optimal time for sanitation felling in Gremmeniella-infected areas. In southern and central Sweden most conidia are dispersed earlier, between April and July, and sporulation ends already in August (Hellgren and Barklund 1992). Once a month between September 2003 and April 2004, two to three of the selected trees were cut down and debranched along the stems.…”
Section: Introductionmentioning
confidence: 99%
“…Our results strongly suggest that the degeneration of the pathogen began in the fall of 2007. This two-year life cycle of the anamorph stage is in accordance with studies of G. abietina in Sweden where the pathogen appeared to have a biennial life cycle [10]. In a study similar to ours conducted in Sweden, it was shown that 18-month-old slash produced as much conidia as fresh slash [9].…”
Section: Discussionsupporting
confidence: 91%
“…However, dispersal by means of airborne ascospores is known to occur, which may have implications for the spread of the disease (Section 3.1.2). If conidia are involved, infection usually occurs in early summer, whereas ascospores infect later during the growing period and late in autumn (Skilling, ; Gibbs, ; Laflamme and Archambault, ; Hellgren and Barklund, ).…”
Section: Pest Categorisationmentioning
confidence: 99%
“…Ascospores of the European race (see Section 3.1.3 on Intraspecific diversity) were originally thought to be absent or rare (EPPO, 1997), although this statement was provided without reference. In fact, apothecia were produced abundantly on diseased Pinus contorta plantations in northern Sweden (Karlman et al, 1994;Hamelin et al, 1996) and on Pinus sylvestris in southern Sweden (Hellgren and Barklund, 1992). The high apothecial production may have been favoured by a longlasting and deep snow cover (Hamelin et al, 1996).…”
Section: Conclusion Of Pest Categorisation (Section 4)mentioning
confidence: 99%